Theory and Experiment in the work of Alonzo Church and Emil Post - De Mol, Liesbeth (unpublished, 2006)
While most mathematicians would probably agree that experimentation together with an empirical attitude both understood in their most general sense can be important methods of mathematical discovery, this is often obscured in the final presentation of the results for the sake of mathematical elegance. In this paper it will be shown how this method has played a significant role in the work of two major contributors to the rather abstract discipline called mathematical logic, namely Alonzo Church and Emil Post.